Sentencing and Prior Convictions: The Past, The Future, and the End of the Prior-Conviction Exception to Apprendi - King, Nancy J. (2014)
This article traces the fascinating history of early efforts to identify defendants and their prior convictions as well as the evolving use of prior convictions in aggravating punishment; examines how contemporary repeat offender penalties fall short of punishment goals and contribute to the racially lopsided profile of punishment today; and critiques potential justifications for the prior conviction exception to the rule in Apprendi v. New Jersey, arguing that the exception should be abandoned. The article summarizes empirical research testing the relationship between prior convictions and examining the efficacy of repeat offender sentences in reducing recidivism; collects commentary on the use of risk prediction in sentencing; surveys state-by-state eighteenth century authority that belies the claim that denying element status to prior convictions that raise the range of punishment is a longstanding tradition; evaluates the weaknesses of the case law underlying the Court's decision in Almendarez-Torres; argues that defendants need not be prejudiced when prior convictions are treated as elements; and observes that the original reason that a very small number of states in the nineteenth century stopped requiring prior convictions to be treated as elements – namely, that an offender’s criminal history was often unknown unless or until a warden recognized him – no longer exists. An earlier version of the article was delivered as the Barrock Lecture on Criminal Law at the Marquette University Law School